First detection of Flavobacterium psychrophilum in juvenile Siberian sturgeons ( Acipenser baerii ) and description of the pathological findings - Chinchilla Rodríguez, Blanca; Vázquez Fernández, Esther; Rebollada Merino, Agustín Miguel; Pérez Sancho, Marta; Domínguez Rodríguez, Lucas José; Rodríguez Bertos, Antonio Manuel (Journal of Fish Diseases, 2023)
Flavobacterium psychrophilum affects many cultured fish species and is considered one of the most important bacterial pathogens causing substantial economic losses in salmonid aquaculture worldwide. Here, F. psychrophilum was identified by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) and nested PCR as the aetiological agent causing mortality in diseased juvenile Siberian sturgeons (Acipenser baerii) reared on a freshwater fish farm. Diseased sturgeons were lethargic and displayed dark skin pigmentation, increased mucus production and the presence of skin ulcerations and haemorrhages specially on the ventral side and the base of fins. The histological examination of fish revealed proliferative branchitis, ulcerative and necrotizing dermatitis and myositis, lymphoid tissue atrophy, liver and kidney degeneration and thrombosis. To the best of our knowledge, this is the first report describing the infection of Siberian sturgeons by F. psychrophilum. The detection of F. psychrophilum in diseased Siberian sturgeons and the description of the pathological findings observed during the outbreak may contribute to a better understanding of the bacterium pathogenicity and the range of fish species susceptible to infection. European Commission Ministerio de Ciencia, Innovación y Universidades (España) Depto. de Sanidad Animal Depto. de Medicina y Cirugía Animal Centro de Vigilancia Sanitaria Veterinaria (VISAVET) Fac. de Veterinaria TRUE pub